WATER DISPENSER: A UNIQUE INNOVATIVE DESIGN THAT MATTERS - Eugenio A. Ermac; Nolasco K. Malabago (European Scientific Journal, ESJ, 2015)
Any individual is basically moved to do a particular task when in need or when challenged by the environment (Amabile, 2013). Cebu Technological University had been experiencing scarcity of instructional equipment for the last decade due to budget constraint. To enhance its instruction for the students in refrigeration and air conditioning majors both for industrial technology and mechanical engineering, the study was conducted making use of stock scrap water dispenser. Innovative design, construction and function were validated and results revealed that the design of water dispenser was Highly Acceptable implying that the design meets the required competency (Friedman, 2003). It increases the students’ performances during pre-test (moderately satisfactory and effective) to very satisfactory and highly effective in the post test after having a practical application on the use of the innovative water dispenser. Thus, an innovative design is recommended to be utilized and duplicated for similar use.